INDONESIA â€“ TAIWAN ECA : A NEED OF STRONG POLICY ACTIONS - Pattiradjawane, Rene. L (Pusat Penelitian Politik, 2015)
This review discuss about the feasibility of economic cooperation agrrement between Indonesia and Taiwan (Republic of China). Although Indonesia do not have yet diplomatic relation with Taiwan, but in the economic context, Taiwan is one of important economic partner for Indonesia, since investment activity and trade between two countries are flourishing. This study promotes that the establishment of Economic Cooperation Agreement (ECA) between Indonesia and Taiwan will strengthen investment flows and enhance Indonesia-Taiwan economic relations. Besides, ECA will be considered as a fesible policy for both sides. The problem in enhancing further bilateral cooperation is the One China Policy. Because of the changing of geopolitical conditions in East Asia, Indonesia needs to consider the opportunity to reformulate the â€œOne China Policyâ€ and takes strong policy action in their relations.Â Keywords: Economic Cooperation Agrrement, Indonesia-Taiwan Relation, One China Policy.Â